Correction: A facile method to synthesize [A′(D′AD)2]-based push–pull small molecules for organic photovoltaics. Issue 109 (11th November 2016) - Shaker, Mohamed; Lee, Jong-Hoon; Trinh, Cuc Kim; Kim, Wonbin; Lee, Kwanghee; Lee, Jae-Suk
Abstract : Correction for "A facile method to synthesize [A′(D′AD)2 ]-based push–pull small molecules for organic photovoltaics" by Mohamed Shaker et al., RSC Adv., 2015, 5, 66005–66012.